Mimicking light-sensing chromophore in visual pigments and determination isomerization site. (April 2020) - Li, Yang; Lan, Haichuang; Yan, Xia; Shi, Xiaotao; Liu, Xiao; Xiao, Shuzhang
Abstract: Three retinal derivatives are designed and synthesized under the inspiration of natural visual pigments. The retinal derivative V3 (retinal-phenylenediamine) is able to respond sensitively to visual light in the absence of a protein environment through isomerization and deprotonation. The response process is applied to verification of information security. Highlights: The charge distribution in retinal molecules was effectively regulated by straightforward backbone modifications. Retinal derivative achieved effective response to visible light through multiple processes in absence of protein environment. A preliminary application based on V3, information security verification is also implemented.